Peran Motivasi Investasi sebagai Mediator dalam Hubungan Literasi Keuangan, Persepsi Risiko, dan Minat Investasi Saham - Ibnu Cahyo Ramadhan; Muhammad Edy Supriyadi (ARBITRASE: Journal of Economics and Accounting, 2026)
This study aims to analyze the influence of financial literacy and risk perception on stock investment interest, with investment motivation serving as a mediating variable among Management Study Program students. The study is motivated by the relatively low level of students' interest in investing in the capital market despite the increasing availability of investment information and financial education. This research employed a quantitative approach using a survey method. Primary data were collected through questionnaires distributed to 200 Management Study Program students selected using a purposive sampling technique. Data were analyzed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method with the assistance of SmartPLS software. The findings indicate that financial literacy has a positive and significant effect on investment motivation (t-statistic = 7.215 > 1.96) and stock investment interest (t-statistic = 4.892 > 1.96). Risk perception has a negative and significant effect on investment motivation (t-statistic = 3.564 > 1.96) as well as stock investment interest (t-statistic = 2.981 > 1.96). Furthermore, investment motivation has a positive and significant effect on stock investment interest (t-statistic = 6.104 > 1.96). The mediation analysis reveals that investment motivation significantly mediates the relationship between financial literacy and stock investment interest (t-statistic = 4.115 > 1.96), as well as the relationship between risk perception and stock investment interest (t-statistic = 2.754 > 1.96). This study contributes theoretically by strengthening the Theory of Planned Behavior and Behavioral Finance Theory through empirical evidence of the mediating role of investment motivation. Practically, the findings are expected to provide valuable insights for higher education institutions, the Financial Services Authority (OJK), the Indonesia Stock Exchange (IDX), and securities companies in designing more effective financial literacy and investment education programs to enhance young people's participation in the capital market.